Handel lwowski w okresie międzywojennym - Bezsmertnyi, Andrij (Dzieje Najnowsze, 2015)
Lwów Trade in the Inter–war Period The article focuses on the history of domestic trade in Lwów during the inter–war period. The author examined the state of trade in the town prior to the First World War by analysing the dynamic of the changing number of commercial enterprises in 1921–1939, and that of professionally active persons and independent employees involved in commerce. Upon the basis of assorted statistical material the article explains the ethnic–religious structure of the traders as well as their specialisations. The author also analysed the size of the enterprises in question and studied marketing methods applied by merchants for the purpose of developing their business ventures. Finally, the analysis encompasses mutual relations of various groups of traders (i.a. the negative attitude towards Jewish merchants in the second half of the 1930s). The last part of the article outlines the policy pursued by the state and the local authorities towards traders.